Utilization of BPJS Health in the hearLIFE Hearing Aid Procurement Process - Andini, Tri (Jurnal Kesehatan Masyarakat Perkotaan, 2026)
BPJS Kesehatan is a government policy in the health sector, one of the BPJS Kesehatan programs is the procurement of hearing aids that have been regulated in the Regulation of the Minister of Health using the NonINA-CBG Tarif. Hearing loss is a shared responsibility between the government and the community. The state plays a crucial role in ensuring access to health services for all citizens. This study aims to utilize BPJS Kesehatan's knowledge in the hearing aid procurement process using quantitative methods and descriptive approaches, sampling through purposive sampling techniques with a sample size of 78 respondents.The results of the study showed that the number of female respondents was higher, namely 60.3%. The highest age was in the 70-74 age group at 19.2%, the highest number of hearing disorders was known in moderate deafness (41-70 dB) at 46.2%. Patient knowledge of the existence of BPJS services was known to be 96.2% who knew about this service, as many as 78.2% felt helped using hearing aids and all respondents knew about how to use and service services if the hearing aid had problems. From this study, it is hoped that there will be more information about BPJS services for all BPJS Kesehatan service users, and the government can increase the NonINA-CBG tariff for hearing aids, so that they are available for various types of hearing disorders, and services for patients using hearing aids can be improved.